Chemoselective Vicinal Dichlorination of Alkenes by Iron Ligand-to-Metal Charge-Transfer Catalysis - Stahl, Jessica; Reiter, Thilo; König, Burkhard (Synlett, 2024)
We report the photocatalytic functionalization of terminal alkenes to vicinal dichlorides by using visible light and FeCl3 as a catalyst, LiCl as a chloride source, and air as an oxidant. The transformation is proposed to be initiated by ligand-to-metal charge-transfer bond homolysis of a Fe–Cl bond, giving a highly reactive chloride radical able to initiate the functionalization of olefins. The process shows high chemoselectivity and broad functional-group tolerance with yields of up to 94% under mild conditions.
Keywords: iron catalysis; photocatalysis; ligand-to-metal charge transfer; chlorination; alkenes; vicinal dichlorides